SISTEM PAKAR UNTUK PENANGANAN PENYAKIT PADA DURIAN MONTONG (Information Technology and Telematics, 2014)
Abstract - At present, the farmers began to realize that cultivate durian is very promising montong or can provide great benefits. That is of course if montong durian cultivated in the right way, which means the main condition to get a big advantage in the cultivation of durian montong lies in its management. Until now, farmers often suffered losses due to frequent montong durian durian eaten by pests montong because farmers still use the manual to find out about the montong durian crop pests. System development methods used in this study is an expert system that consists of the identification, conceptualization, formalization, implementation, evaluation and development system. System design using the Levelled DFD context diagram and consists of Level 0 DFD and ERD. The application development using PHP and MySQL database. The end result of this research is an expert system for disease management in web-based montong durian can be used to solve the problem of the diagnosis of diseases in durian montong, because it can provide a diagnosis of any type of disease Keywords – Expert System, Durian Montong, PHP, MySQL